Measurement of electrons from heavy-flavour decays in pp and Pb-Pb collisions with ALICE at the LHC - Kweon, MinJung (Nuclear physics. A, Nuclear and hadronic physics, 2013)
The ALICE experiment has measured at mid-rapidity electrons from heavy-flavour decays in pp collisions at S=2.76 and 7 TeV, and in Pb-Pb collisions at SNN=2.76 TeV. In pp collisions, electrons from charm-hadron and from beauty-hadron decays are identified by applying cuts on displaced vertices. Alternatively the relative yield of electrons from beauty decays to those from heavy-flavour decays is extracted using electron-hadron correlations. Results are compared to pQCD-based calculations. In Pb-Pb collisions, the pT dependence of the nuclear modification factor of electrons from heavy-flavour decays is presented in two centrality classes. The status of the analysis of electrons from beauty decays in Pb-Pb collisions is reported, in view of the measurement of the corresponding nuclear modification factor.
Gesehen am 08.09.2021